Synthesis of a magnetic π-extended carbon nanosolenoid with Riemann surfaces - Wang, Jinyi; Zhu, Yihan; Zhuang, Guilin; Wu, Yayu; Wang, Shengda; Huang, Pingsen; Sheng, Guan; Chen, Muqing; Yang, Shangfeng; Greber, Thomas; Du, Pingwu (Nature communications, 2022)
Riemann surfaces are deformed versions of the complex plane in mathematics. Locally they look like patches of the complex plane, but globally, the topology may deviate from a plane. Nanostructured graphitic carbon materials resembling a Riemann surface with helicoid topology are predicted to have interesting electronic and photonic properties. However, fabrication of such processable and large π-extended nanographene systems has remained a major challenge. Here, we report a bottom-up synthesis of a metal-free carbon nanosolenoid (CNS) material with a low optical bandgap of 1.97 eV. The synthesis procedure is rapid and possible on the gram scale. The helical molecular structure of CNS can be observed by direct low-dose high-resolution imaging, using integrated differential phase contrast scanning transmission electron microscopy. Magnetic susceptibility measurements show paramagnetism with a high spin density for CNS. Such a π-conjugated CNS allows for the detailed study of its physical properties and may form the base of the development of electronic and spintronic devices containing CNS species. Fabrication of large π-conjugated carbon nanosolenoid materials with helicoid topology remains a challenge. Here the authors demonstrate synthesis of a metal-free π-extended carbon nanosolenoid material with a helical structure, exhibiting unique photophysical and magnetic properties.